Effectiveness of Gibberellin Concentration (GA3) for The Growth and Propagation of Plant Cuttings Stevia Rebaudiana - Pasaribu, Pinta Omas; Saputro, Sigit; Indrayanti, Reni; Adisayhputra, Adisayhputra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Stevia (Stevia rebaudiana) is a perennial semi-herbaceous plant whose leaves can be used as a sweetener for food and beverages. Stevia sweetener has low calories so its use is not bad for health. Propagation of Stevia by stem cutting using the top is a simple, fast, and easy propagation technique. This study aimed to obtain the optimum concentration of GA3 and the correct propagation method for Stevia cuttings for lowland areas. The research was conducted at the Green House, Biology Study Program FMIPA UNJ. The method used was an experimental method with a completely randomized design, consisting of 3 experiments, namely the provision of GA3 with a dose of 10 ppm, 30 ppm, and 50 ppm. Qualitative data were processed descriptively, quantitative data were analyzed based on ANOVA. The results showed that the use of Gibberellins with a concentration of 10 ppm and the maintenance of Stevia cuttings in clear plastic containers were more effective in the development of an average stem length of 19.18 ± 2.40, a mean plant length of 23.62 ± 2.34 and an average number of roots 14, 33 ± 2.32.